Exploring the Vibrational Side of Spin‐Phonon Coupling in Single‐Molecule Magnets via 161Dy Nuclear Resonance Vibrational Spectroscopy. Issue 23 (24th April 2020) - Scherthan, Lena; Pfleger, Rouven F.; Auerbach, Hendrik; Hochdörffer, Tim; Wolny, Juliusz A.; Bi, Wenli; Zhao, Jiyong; Hu, Michael Y.; Alp, E. Ercan; Anson, Christopher E.; Diller, Rolf; Powell, Annie K.; et al.
Abstract: Synchrotron‐based nuclear resonance vibrational spectroscopy (NRVS) using the Mössbauer isotope 161 Dy has been employed for the first time to study the vibrational properties of a single‐molecule magnet (SMM) incorporating Dy III, namely [Dy(Cy3 PO)2 (H2 O)5 ]Br3 ⋅2 (Cy3 PO)⋅2 H2 O ⋅2 EtOH. The experimental partial phonon density of states (pDOS), which includes all vibrational modes involving a displacement of the Dy III ion, was reproduced by means of simulations using density functional theory (DFT), enabling the assignment of all intramolecular vibrational modes. This study proves that 161 Dy NRVS is a powerful experimental tool with significant potential to help to clarify the role of phonons in SMMs. Abstract : Bad vibrations? 161 Dy nuclear resonance vibrational spectroscopy gives direct experimental access to the partial phonon density of states which includes all vibrational modes involving a displacement of the Dy III ion. In combination with density functional theory, an assignment to all intramolecular vibrational modes is possible, paving an ideal path to help to clarify the role of phonons in single‐molecule magnets.